Selective separation of phenolic compound using molecular imprinting technique for solid phase extraction - Nadiah, Zainuldin (2010)
The objectives of this research are to study the performance of molecular imprinted polymer(MIP)in solid phase extraction (SPE) process and to determine the formulation for preparing of MIP particle and also to analyze the absorbance differences between polymer and silica.As we know,cocoa contained much higher levels of total phenolic compounds such as phenol.Phenolic compounds are widely distributed in the plant kingdom.This study is basically to adsorb phenol using molecular imprinting technique for solid phase extraction.They are two parameters used which are adsorbent amount and concentration of phenol solution to observe their effects of absorbance percentage and absorbance capacity. Furthermore,for adsorbent amount used in this study are 2g, 4g,6g and 8g while the concentration of phenol used are 100mg/L, 200mg/L, 300mg/L, 400mg/L and 500mg/L.From the experimental result,it showed that the optimum adsorbent amount in this experiment is 5g while the optimum concentration of phenol is 300mg/L.Besides,the technique used in this study is molecular imprinting technique to prepare MIP particle for solid phase extraction.The successful preparation of molecularly imprinted polymers for solid phase extraction provides an innovative opportunity for the development of advanced adsorption phenolic compound in plant.The experimental results clearly showed that higher adsorbent amount and higher concentration of phenol solution gave higher absorbance.The experimental results clearly showed that higher adsorbent amount and higher concentration of phenol solution gave higher absorbance.A higher selectivity of target molecule proved when performing the extraction using polymer.